AHP Method for Selecting Wood As Furniture Raw Material - Gatot Setiawan; Imam Husni Al Amin (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2020)
Wood is an important element determining the quality of a product on furniture. The lack of knowledge of the furniture industry in this industry causes problems to choose a decision in determining the wood material to produce quality and quality furniture products. Development of a decision support system using the Analytichal Hierarchy Process method uses wood quality feasibility parameters consisting of five criteria, namely Physical Physical Properties, Mechanical Mechanical Properties of Wood, Wood Grade, Wood Age and Wood Substance from several samples. The results of this study were to produce a decision from the data to determine a decision, a decision support system for the purchase of wood materials for a furniture industry company using the Analytichal Hierarchy Process method. After testing, it can be concluded that the decision obtained is appropriate for use by staff and superiors and is ready to be implemented.